PENGARUH FINANCIAL LITERACY, PEER INFLUENCE, DAN FINTECH PAYMENT TERHADAP FINANCIAL MANAGEMENT BEHAVIOR PADA MAHASISWA PRODI PENDIDIKAN EKONOMI IKIP PGRI BOJONEGORO - Khotijah, Vina St; Jehan, Adam; Mujahidin, Ali; Rohman, Nur (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2025)
The research investigates the impact of fiscal acumen, collegial persuasion, and financial technology disbursement on monetary administration conduct among tertiary learners. It addresses the imbalance between the widespread use of financial technology and inadequate financial literacy, along with peer pressure influences. Using an elucidatory methodology with a quantitative paradigm, 73 respondents were selected from a pool of 268 scholars through judgmental sampling. Data were collected via Google Forms and analyzed using multivariate linear regression with SPSS 27, including validity, reliability, classical assumptions, T-tests, F-tests, and determination analyses. Findings indicate that fiscal acumen and financial technology disbursement significantly influenced financial behavior, while collegial persuasion did not. However, all three variables together had a substantial positive impact.